The Effectiveness of Educandy Media through Differentiated Learning on the Learning Participation of Slow Learner Elementary School Students - Ivandy Prayuda Pratama; Minsih Minsih (Journal of Educational Sciences, 2026)
Learning participation among Slow Learner students in elementary schools tends to remain low when instruction is delivered uniformly without considering differences in learning readiness. This study aims to examine the effectiveness of Educandy media integrated with differentiated learning in improving learning participation among Slow Learner students in elementary schools. The research employed a quantitative quasi-experimental design with a pretest-posttest control group. Two fourth-grade classes were selected through purposive sampling, with analysis focused on identified Slow Learner students. Data were collected using a structured learning participation questionnaire. Statistical analysis included normality testing and nonparametric tests to determine differences within and between groups. The results showed a significant increase in learning participation in the experimental class compared to the control class, particularly among Slow Learner students. These findings indicate that integrating digital game-based media within a differentiated learning framework provides an adaptive and inclusive approach that effectively enhances student participation in elementary school classrooms.